2007
DOI: 10.1111/j.1440-1754.2007.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

High volume‐low intensity exercise camp and glycemic control in diabetic children

Abstract: With a low rate of hypoglycaemia crisis and better glycemic control the proposed programme was found to be satisfactory but the downside was that the duration of the effects was too short. With no participation in organised exercise programmes and with absence of controlled nutrition, the beneficial effects of the camp disappeared within 2 months after the camp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
0
32
0
3
Order By: Relevance
“…The length of interventions ranged from 2 to 39 weeks . The modal duration of intervention was 12 weeks .…”
Section: Resultsmentioning
confidence: 99%
“…The length of interventions ranged from 2 to 39 weeks . The modal duration of intervention was 12 weeks .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated a direct association between glycemic control and physical activity (16,31) and cardiorespiratory fitness (11). Aman and colleagues (1) found that a reduction of sedentary activities through an increase in physical activity was associated with improved glycemic control and reduced levels of HbA1c.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1950s, Joslin proposed that exercise is the third essential component in blood glucose regulation for persons with type 1 diabetes (T1D), after insulin and dietary management. Although most studies have shown little impact upon hemoglobin A1c (HbA1c) levels , and many only a brief improvement unless the exercise was sustained for 6 months , a cross‐sectional analysis of data on a larger group showed that the frequency of regular physical activity was associated with lower HbA1c without increasing the risk of severe hypoglycemia . Younk et al have provided a useful review .…”
Section: Introductionmentioning
confidence: 99%